Determination of trace concentrations of bromophenols in water using purge-and-trap after in situ acetylation - Blythe, Justin; Heitz, Anna; Joll, Cynthia; Kagi, Robert (Elsevier, 2006)
An analytical method that enables detection and quantification of bromophenols (BPs) at taste threshold concentrations (2,6-DBP: 0.5 ng/L) was developed. This method involves conversion of the BPs to their acetates, followed by isolation of the acetates by a modified purge-and-trap procedure, and analysis by gas chromatography-mass spectrometry (GC-MS) in selected ion monitoring (SIM) mode. Bromophenyl acetates were synthesizcd so that each of the two steps in the method could be developed and optimised in isolation to the other. Deuterated BPs (phenol-d(5), 2-BP-d(4), 4-BP-d(2), 2,6-DBP-d(3),2,4-DBP-d(3) and 2,4,6-TBP-d(2)) were synthesized to enable quantification of analytes using the deuterated analogues of analytes as internal standards. This method allowed quantification of BPs at concentrations ranging from the detection limits (3 ng/L for phenol and 0.1-0.5 ng/L for each of the BPs) to 1000 ng/L for each analyte, with repeatabilities of <= 14% (RSD) for concentrations of 1 ng/L and <= 9% (RSD) for concentrations of 10-1000 ng/L, with recoveries ranging from 91 to 97%.